O-003 IMS3 Like Subgroup Analysis in the North American SOLITAIRE Stent-Retriever Acute Stroke Registry. (14th July 2013) - Nogueira, R; Castonguay, A; Gupta, R; Sun, C; Martin, C; Holloway, W; Mueller-Kronast, N; English, J; Linfante, I; Dabus, G; Malisch, T; Bozorgchami, H; et al.
Abstract : Introduction/Purpose: IMS3 demonstrated no significant difference between treatment with IV-rtPA alone or IV-rtPA plus IA therapy. However, the trial included only earlier generations of thrombectomy devices and did not evaluate the efficacy of newer devices. Here, we present data on an "IMS-III-Like group" from The North American SOLITAIRE Acute Stroke (NASA) Registry, a repository database of the newer generation Solitaire Stent-retriever. An exploratory analysis was performed to compare these results to the IMS3 IV and IV/IA groups. Materials and Methods: The investigator-initiated NASA Registry recruited sites to submit data on consecutive patients treated with Solitaire-FR. A cohort similar to the IMS-III IV-rtPA+Solitaire-FR population (NASA-IMS3 Matched Group (NIMG)) was identified and compared to the recently published results of the IMS3 IV and IV/IA groups. Good clinical outcome was defined as a 90-day mRS ≤2. Successful recanalisation was defined as TIMI ≥2. SICH was defined as any parenchymal haematoma, SAH, or IVH associated with a worsening of the NIHSS score by 4 or more within 24 hours. Results: 354 acute ischaemic stroke patients were enrolled in the NASA Registry from 24 centres. The cohorts were comprised of: 156 NIMG versus 434 and 222 in the IMS3 IV/IA and IV only groups, respectively. Baseline demographics were similar between cohorts: Median age 70 (NIMG); 69 (IMS3 IV/IA); 70 (IMS3 IV). Initial median NIHSS was higher in NIMG (19) compared to the IMS3 IV/IA (17) and IMS3 IV groups (18). mTICI > 2b rate was 69.9% in NIMG versus 39.6% in the IMS III IV/IA. Interestingly, mTICI 3 rate was 41% in NIMG vs 2.2% in the IMS III IV/IA group. The 90-day mRS outcome was available in 88.5% (138/156) of NIMG patients. A good outcome of mRS?2 was demonstrated in 51.5% (71/138), compared to 40.8% (169/415) in IMS3 IV/IA and 38.7% (83/215) in IM3 IV alone groups. 90-day mortality was 24.6% in NIMG versus 19.1% and 21.6% in IMS3 IV/IA and IV alone groups, respectively. Conclusion: In the NASA registry, the NASA-IMS3 Matched Group (NIMG) demonstrated a higher rate of good clinical outcome (51.5%) compared to the IMS3 IV/IA (40.8%) and IV alone (34.6%) groups. Disclosures: R. Nogueira: None. A. Castonguay: None. R. Gupta: None. C. Sun: None. C. Martin: None. W. Holloway: None. N. Mueller-Kronast: None. J. English: None. I. Linfante: None. G. Dabus: None. T. Malisch: None. H. Bozorgchami: None. A. Xavier: None. A. Rai: None. M. Froehler: None. A. Badruddin: None. T. Nguyen: None. M. Taqi: None. M. Abraham: None. V. Janardhan: None. H. Shaltoni: None. A. Yoo: None. A. Abou-Chebl: None. P. Chen: None. O. Zaidat: None.